2020
DOI: 10.21037/jtd-20-1116
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopy for lung cancer: who is the future of thoracic surgery?

Abstract: Lung cancer is one of the most commonly diagnosed cancer with an estimated 228,820 new cases in 2020, representing 12.67% of all new cancer cases (1). According to a systemic global cancer study, lung cancer is the main cause for cancer deaths, with 1.9 million deaths worldwide (2). Due to the high incidence and mortality, lung cancer has become a heavy burden on public health. However, with the extensive use of low-dose computed tomographic screening, more patients with operable lung cancer (stages IA-IIIA) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
(40 reference statements)
0
15
0
3
Order By: Relevance
“…Video-assisted thoracic surgery (VATS) lobectomy has become the standard procedure for treating early-stage non-small cell lung cancer (NSCLC) ( 1 ). Currently, for some specific early-stage lung cancer, VATS segmentectomy through fine anatomy can not only achieve the same therapeutic effect as VATS lobectomy but also further preserve normal lung tissue, thereby maximizing the preservation of lung function ( 2 ). However, the surgical difficulty and complexity of VATS segmentectomy are much higher than those of VATS lobectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Video-assisted thoracic surgery (VATS) lobectomy has become the standard procedure for treating early-stage non-small cell lung cancer (NSCLC) ( 1 ). Currently, for some specific early-stage lung cancer, VATS segmentectomy through fine anatomy can not only achieve the same therapeutic effect as VATS lobectomy but also further preserve normal lung tissue, thereby maximizing the preservation of lung function ( 2 ). However, the surgical difficulty and complexity of VATS segmentectomy are much higher than those of VATS lobectomy.…”
Section: Introductionmentioning
confidence: 99%
“…A lobectomy is considered the gold standard of care for healthy individuals with early-stage lung cancer ( Hartwig and D'Amico, 2010 ). Modern surgical techniques, such as minimally invasive video-assisted thoracoscopic surgery (VATS) for lung resections, are enabling better prognosis for patients and better operation conditions for surgeons, redefining surgical fitness ( Jiang et al, 2020 ). In some studies, perioperative mortality and long-term survival following VATS lobectomy were found to be superior to those following open surgery ( Jones and Baldwin, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The RATS system is comprised of a remote console and three or four robotic arms capable of simulating surgeon movements. In addition, it provides surgeons with a magnified three-dimensional (3D) and high-definition operation field, which enables them to perform more complex procedures ( Jiang et al, 2020 ). However, because of the novel surgical technique, the cost is higher.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic-assisted thoracic surgery (RATS), an innovative minimally invasive surgery system, provides a magnified, 3D, high-definition surgical field for operating surgeons, allowing them to perform complicated surgery without dissecting unnecessary surrounding tissue (4,5). Moreover, the maneuverability of the mechanical wrist, which is superior to that of human hand, makes radical lymphadenectomy easier (4,5). Therefore, RATS may be especially suitable for patients with nodal involved disease.…”
Section: Introductionmentioning
confidence: 99%